The Effects Of Actıvator And Actıvator + Anterıor Hıgh-Pull Headgear On The Growth Dırectıon Of Class 2 Cases - Oktay Üner; Sevil Akkaya; Füsun Buyruk (Galenos Yayinevi, 1989)
In this study which the effects of activator and activator + anterior high-pull headgear on the growth direction of skeletal class 2 cases for a period of aproximately 9 months; 33 cases having a mean age of 10.59 years; ANB angles 4.5 degrees and over were studied. Activator treatment has been applied to the 11 of the 22 treatment cases, the others have had the activator + anterior high-pull headgear treatment. The control group, 11 patients, has only been observed in terms of the growth and development without having any treatment. At the end of the study; it was found that the decrease in ANB angle and the increase in SL dimension in the treatment groups: the increase in anterior lower face height in the activator group and the increase in the ratio of posterior to anterior face height were statistically significant.